Results of 5-year follow-up study in patients with peripheral artery disease treated with PL-VEGF165 for intermittent claudication. (September 2018) - Deev, Roman; Plaksa, Igor; Bozo, Ilia; Mzhavanadze, Nina; Suchkov, Igor; Chervyakov, Yuriy; Staroverov, Ilia; Kalinin, Roman; Isaev, Artur
Background: The effective treatment of chronic lower limb ischemia is one of the most challenging issues confronting vascular surgeons. Current pharmacological therapies play an auxiliary role and cannot prevent disease progression, and new treatment methods are needed. In 2011, a plasmid VEGF65-gene therapy drug was approved in Russia for the treatment of chronic lower limb ischemia (ClinicalTrials.gov identifier: NCT03068585). The objective of this follow-up study was to evaluate the long-term safety and efficacy of gene therapy in patients with limb ischemia of atherosclerotic genesis. Aims: To evaluate the long-term safety and efficacy of the therapeutic angiogenesis, 36 patients in the treatment group (pl- VEGF165 ) and 12 patients in the control group participated in a 5-year follow-up study. Planned examinations were carried out annually for 5 years after pl- VEGF165 administration. Results: Differences in the frequency of major cardiovascular events (pl- VEGF165 5/36 versus control 2/12; p = 0.85), malignancies (pl- VEGF165 1/36 versus control 0/12; p = 0.38) and impaired vision (there was none in either group) over the 5-year follow-up period did not achieve statistical significance. The target limb salvage was 95% ( n = 36) and 67% ( n = 12) in the pl- VEGF165 and control groups, respectively. The pain-free walking distance value increased by 288% from 105.7 ± 16.5 m to 384 ± 39 m in the treatment group by the end of the fifth year, with a peak of 410.6 ± 86.1 m achieved by the end of the third year. The ankle-brachial index (ABI) increased from 0.47 ± 0.01 to 0.56 ± 0.02 by the end of the first year, with a subsequent slight decrease to 0.51 ± 0.02 by the fifth year. The maximum increment of transcutaneous oximetry test (tcoO2 ) by 36%, from 66.6 ± 3.7 mm Hg to 90.7 ± 4.9 mm Hg, was observed by the end of the second year. Conclusion: The therapeutic effect of angiogenesis induction by gene therapy persists for 5 years.